Chemokine receptors (version 2020.5) in the IUPHAR/BPS Guide to Pharmacology Database. (2020) - Bachelerie, Francoise; Ben-Baruch, Adit; Burkhardt, Amanda M.; Charo, Israel F.; Combadiere, Christophe; Förster, Reinhold; Farber, Joshua M.; Graham, Gerard J.; Hills, Rebecca; Horuk, Richard; Locati, Massimo; Luster, Andrew D.; et al.
No abstract available